Circulating tumor cell analysis in locally advanced and metastatic squamous cell carcinoma of the head and neck. Issue 6 (27th October 2020) - Harris, Ethan J.; Huang, Julian; Carroll, Erin; Lowe, Alarice C.; Chau, Nicole G.; Rabinowits, Guilherme; Haddad, Robert; Hanna, Glenn J.; Haddad, Tyler; Sanborn, Matthew; Kacew, Alec; Lorch, Jochen
Abstract: Background: Circulating tumors cells (CTCs) are considered an early step towards metastasis and have been linked to poor prognosis in several types of cancer. CTCs in squamous cell carcinoma of the head and neck (SCCHN) have an unclear role. Methods: In this prospective study, patients with locally advanced or metastatic SCCHN had CTC counts assessed before starting systemic treatment using the CellSearch System. Select cases also had sequential CTC evaluation. Presence of CTCs was correlated with patient characteristics and outcomes. Results: Forty‐eight patients enrolled, and 36 had evaluable clinical data and baseline CTC counts. Twenty‐five patients had locally advanced disease (LAD) and 11 had metastatic disease. ≥1 CTCs were detected in six patients with LAD (24%) and four with metastatic disease (36%). On univariate analysis, smoking was associated with CTCs. Conclusion: CTCs are not associated with prognosis in patients with LAD and metastatic disease; however, they are present in this patient population, and ≥1 CTCs is associated with a history of smoking. Level of evidence: 1b; individual prospective cohort study. Abstract : Circulating tumors cells (CTCs) were detected in 6/25 patients with locoregionally advanced disease (24%) and 4/11 with metastatic squamous cell carcinoma of the head and neck (36%). On univariate analysis, smoking was associated with CTCs.